Beyond the One Gene–One Disease Paradigm: Complex Genetics and Pleiotropy in Inheritable Cardiac Disorders. Issue 7 (13th August 2019) - Cerrone, Marina; Remme, Carol Ann; Tadros, Rafik; Bezzina, Connie R.; Delmar, Mario
Abstract : Inheritable cardiac disorders, which may be associated with cardiomyopathic changes, are often associated with increased risk of sudden death in the young. Early linkage analysis studies in Mendelian forms of these diseases, such as hypertrophic cardiomyopathy and long-QT syndrome, uncovered large-effect genetic variants that contribute to the phenotype. In more recent years, through genotype-phenotype studies and methodological advances in genetics, it has become evident that most inheritable cardiac disorders are not monogenic but, rather, have a complex genetic basis wherein multiple genetic variants contribute (oligogenic or polygenic inheritance). Conversely, studies on genes underlying these disorders uncovered pleiotropic effects, with a single gene affecting multiple and apparently unrelated phenotypes. In this review, we explore these 2 phenomena: on the one hand, the evidence that variants in multiple genes converge to generate one clinical phenotype, and, on the other, the evidence that variants in one gene can lead to apparently unrelated phenotypes. Although multiple conditions are addressed to illustrate these concepts, the experience obtained in the study of long-QT syndrome, Brugada syndrome, and arrhythmogenic cardiomyopathy, and in the study of functions related to SCN5A (the gene coding for the α-subunit of the most abundant sodium channel in the heart) and PKP2 (the gene coding for the desmosomal protein plakophilin-2), as well, is discussed in more detail.